2007
DOI: 10.1097/01.shk.0000239779.25775.e4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Near-Infrared Spectroscopy Measurements in Patients With Severe Sepsis

Abstract: This study evaluated near-infrared spectroscopy (NIRS)-derived measurements in hemodynamically stable patients with severe sepsis, as compared with similar measurements in healthy age-matched volunteers. Prospective, preliminary, observational study in a surgical intensive care unit and clinical research center at a university health center. We enrolled 10 patients with severe sepsis and 9 healthy age-matched volunteers. For patients with severe sepsis, we obtained pulmonary artery catheter and laboratory valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 37 publications
8
104
1
4
Order By: Relevance
“…14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings. Skarda et al 23 found NirVO 2 values of 97 ± 36 U, again in the range seen in our patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…14,15,25,26 In our small series of patients, the microcirculation was moderately to severely compromised, in line with previous studies of patients with severe sepsis and septic shock. 14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings. Skarda et al 23 found NirVO 2 values of 97 ± 36 U, again in the range seen in our patients.…”
Section: Discussionsupporting
confidence: 91%
“…14,22,23 For example, Creteur et al 22 reported NIRS ascending slope values of 2.3 ± 1.3%Ásec -1 in patients with septic shock, a value similar to our findings. Skarda et al 23 found NirVO 2 values of 97 ± 36 U, again in the range seen in our patients. In addition, the proportion of perfused small vessels assessed by SDF imaging was 65% (53.1-68.9%) in patients with septic shock, similar to that reported by Sakr et al 14 As in sepsis, we observed a significant correlation between the microcirculatory abnormalities detected by the two methods (SDF imaging and NIRS) and the severity of disease as assessed by SOFA and APACHE II scores.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In clinical observations involving patients in severe cardiovascular compromise, the THI (alongside other NIRS based parameters) has been demonstrated to be an effective reflection of tissue perfusion blood volume when correlated with established invasive parameters. 26,27 Evidence for the Use of NIRS in TBI As discussed earlier in this review, currently the most popular uses for cerebral NIRS in adult clinical practice are within the context of cardiac and vascular surgery, in which close monitoring of cerebral perfusion is required during periods of cardiopulmonary bypass. These situations most frequently involve normal cerebral anatomy and autoregulation.…”
Section: Davies Et Almentioning
confidence: 99%
“…The specific effect of transfusion was not evaluated in this study, however, as the investigation was designed to assess the overall bundle rather than its component parts. Using Near Infrared Spectroscopy (NIRS) or Sidestream Dark Field (SDF), several investigators have reported that microcirculation is markedly altered in sepsis, that these alterations are more severe in nonsurvivors than in survivors, that persistent microvascular alterations are associated with development of multiple organ failure and death, and that microvascular alterations are the most sensitive and specific predictor of outcome in septic patients [91][92][93][94][95][96][97].…”
Section: Within 6 Hours Of Severe Sepsismentioning
confidence: 99%